Detection of Different Hosts From a Distance Alters the Behaviour and Bioelectrical Activity of Cuscuta racemosa - Parise, André Geremia; Reissig, Gabriela Niemeyer; Basso, Luis Felipe; Senko, Luiz Gustavo Schultz; Oliveira, Thiago Francisco de Carvalho; de Toledo, Gabriel Ricardo Aguilera; Ferreira, Arlan Silva; Souza, Gustavo Maia (Frontiers in Plant Science, 2021)
The behaviour of dodder plants (Convolvulaceae: Cuscuta spp.) have been studied for many years, but many questions remain unanswered. In this work, we studied how the detection by distance of different hosts influence the physiology of C. racemosa. We demonstrate that it changes its foraging strategy depending on the host detected: detection of a host leads to smaller accumulation of photosynthetic pigments, while the absence of hosts leads to increased pigment content. We analysed the electrical signalling of the dodders in the absence and the presence of two different host species. For the analyses, we used electrophytographic techniques and employed analyses of complexity such as PSD, PDF, autocorrelation, approximate entropy and multiscale sample entropy. We also employed different machine learning techniques for searching for patterns in the signals. The results indicate that the events of voltage variation have a pattern of distribution that follows a power law, are scale-invariant, and are related to 1/f noise, to self-organised criticality and present high levels of complexity. We show that the dodder changes its electrophysiological behaviour almost immediately upon detection of a host. The pattern of its electrical signalling is characteristic for each host, suggesting that dodders recognise different species of hosts by distance. Furthermore, the detection of hosts increased the order and decreased the complexity of the signals, suggesting a process of attention towards the host plants. It could be the first empirical evidence for a process of attention in plants.